Structural basis for the activity regulation of Medicago calcium channel CNGC15 - Xia Xu; Qinrui Wang; Tengfei Sun; Heyi Gao; Ruichu Gu; Junzhao Yang; Jiaqi Zhou; Peng Fu; Han Wen; Guanghui Yang (Cell Discovery)
Abstract Cyclic nucleotide-gated ion channels (CNGCs) in plants mediate Ca2+ influx in response to environmental changes. Among numerous plant CNGCs, Medicago truncatula CNGC15a/b/c (MtCNGC15) is localized to the nuclear envelope. The opening and closing cycle of MtCNGC15 is tightly associated with the Ca2+ oscillation in symbiosis. However, the molecular mechanism underlying MtCNGC15 activity regulation remains unclear. In this study, we present the structures of MtCNGC15 in its apo form and in the presence of CaM. The apo MtCNGC15b exhibits a flexible cytoplasmic domain (CPD), whereas binding of the MtCaM inhibits Ca2+ currents and stabilizes the highly dynamic CPD. Furthermore, the activity of MtCNGC15b seems to be independent of cGMP. The hypothetical binding pocket for cGMP is occupied by an arginine residue. These findings elucidate the structural basis for the activity regulation of nuclear localized MtCNGC15.